A GIS-based analysis of the urban green space accessibility in Craiova city, Romania. Issue 1 (2nd January 2020) - Vîlcea, Cristiana; Șoșea, Cristina
ABSTRACT: The population living in large urban areas faces multiple pressures on their physical and psychological well-being coming from various polluting sources: air pollution, water pollution, and high noise level, thermal and visual stress. Urban green spaces have a positive impact on human health, as they help people relax more. Stress relief through physical exercise and social interaction is possible by having an increased access to parks or other green areas. As in the case of many growing cities, Craiova faces a continuous demand for more construction development space, while the shrinkage of urban green areas is becoming an issue. Using a GIS-based method, this study analyses the accessibility of Craiova residents to urban green spaces, identifying the areas with reduced green spaces and making recommendations for the improvement of the green areas available to residents. The number and location of the parks in the city are correlated with the population density within residential areas in order to analyse the accessibility to green areas based on both walking and driving distance between the access points of the green spaces and the residential areas. Data indicate an unevenly distribution of parks and access to green areas.